Weakening of subsurface ocean temperature seasonality over the past four decades - Fukai Liu; Yiyong Luo; Fengfei Song; Wen-Xiao Yu; Jian Lu; Lijing Cheng (Communications Earth & Environment)
Abstract The seasonal cycle, responsible for much of the temperature variability in the upper ocean, exerts profound climatic and ecological influence. While surface intensification of temperature seasonality has been widely examined, changes beneath the ocean surface remain unknown. Here we analyze multiple ocean temperature datasets, revealing a robust, substantial weakening of subsurface seasonality by 5.7 ± 1.8% below the mixed layer in extratropical oceans since the 1980s. Using a hierarchy of climate models and an idealized diffusive model, we attribute this weakening to increased ocean heat uptake driven by rising greenhouse gases. This process strengthens upper ocean stratification, suppresses vertical mixing, and limits heat penetration into deeper ocean layers, resulting in a more quiescent subsurface ocean with reduced seasonal variability. Our findings highlight a new fingerprint of anthropogenic influence on subsurface ocean seasonality, with important implications for ocean biogeochemical processes and marine ecosystems.